Adiponectin-Transfected Endothelial Progenitor Cells Have Protective Effects After 2-Hour Middle-Cerebral Artery Occlusion in Rats With Type 2 Diabetes Mellitus - Wang, Meiyao (Front Neurol, 2021)
Objectives: This present study aimed to examine the effects of adiponectin-transfected endothelial progenitor cells (LV-APN-EPCs) on cerebral ischemia–reperfusion injury in rats with type 2 diabetes mellitus (T2DM) and to explore the underlying mechanisms. Methods: Seventy male Sprague–Dawley rats with T2DM were randomly divided into sham, phosphate-buffered saline (PBS), LV-APN-EPCs, LV-EPCs, and EPCs groups. Transient middle cerebral artery occlusion (MCAO) was induced by the intraluminal suture method. After 1 h of reperfusion, the five interventions were performed by tail-vein injections. The modified neurological severity score (mNSS) was used to assess neurological function before and on days 1, 7, and 14 after MCAO. After 14 days, magnetic resonance imaging scanning, hematoxylin and eosin staining, terminal dUTP nick-end labeling staining, Western blotting analysis, cluster of differentiation (CD) 31 immunofluorescence, and enzyme-linked immunosorbent assay were used to evaluate infarct rate, morphological damage, cell apoptosis, and microvessel density. Results: Compared with PBS, LV-EPCs, and EPCs groups, the LV-APN-EPCs group showed significantly lower mNSS score, lower infarct rate, and less morphological damage (all P < 0.05). In addition, compared with other groups, the LV-APN-EPCs group had significantly increased levels of B cell lymphoma/leukemia-2 (Bcl-2) protein, CD31+ microvessels, endothelial nitric oxide synthase, and vascular endothelial growth factor, and decreased levels of Bcl-2-associated X protein and neuronal apoptosis in the peri-infarct cortex (all P < 0.05). Conclusion: These results suggest that LV-APN-EPCs exert protective effects against cerebral ischemia–reperfusion injury in T2DM rats by increasing angiogenesis.